Party system institutionalization and reliance on personal income tax: Exploring the relationship using new data - Armin von Schiller (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2017)
This paper explores the effect of party system institutionalization on the reliance of tax systems on the personal income tax. As a first step, the paper re-examines the relationship between party system institutionalization and taxation patterns employing the recently launched Government Revenue Dataset. In a second step, the relationship in tested in different country subgroups, based on governance structures, availability of alternative sources of revenue, and geographical location. The main results remain fairly robust using the Government Revenue Dataset: where bureaucratic capacity is low, the effect of party system institutionalization is large and highly significant, whereas where bureaucratic capacity is high this effect disappears. Furthermore, the analysis using the Government Revenue Dataset provides additional insights into the large variance between groups of countries. The results indicate that the effect is particularly strong and robust in democratic regimes and where alternative sources of revenue are abundant. Overall, the findings can be considered to provide additional support for two claims: first, that taxation is best understood as a problem of credible commitment, particularly where bureaucratic capacity tends to be limited, and second, that institutionalized collective actors, such as political parties, play a key role in solving this problem.
Keywords: D31; H24; H26; H30; D72; D78; 330; personal income tax; party system institutionalization; bureaucratic capacity; fiscal contractualism; fiscal capacity